Eksistensi Budaya Maghrib Mengaji Al-Quran Bagi Remaja Perempuan Desa Kalipucang - Darmaningrum, Khaerunnisa Tri; Ainurokhmah, Nabila (IAINU Kebumen, 2025)
Reading the Al-Qur'an is mandatory for every Muslim from young to old, the great benefits gained from reading the Al-Qur'an are closely related to every human being in living their life. Discussing the Al-Qur'an as a guide, to understand the contents of a guide or instruction, you need a way to understand it, namely by reading. Creating a reading culture can be the main task for young people or teenagers. Teenagers need to maintain the culture of reading the Koran. In this research, the data collection process was carried out using qualitative methods. Data collection techniques were obtained by observation, interviews, and documentation. Analysis techniques are carried out by reviewing data, reduction, data presentation, data interpretation, and educational conclusions. From the results of research regarding educational empowerment activities for maghrib culture in reciting the Koran for teenage girls in Kalipucang Village. The results obtained were that empowerment through educational programs for teenage girls increased the motivation and awareness of teenagers about the importance of reciting the Koran and the benefits of reciting the Koran after Maghrib, especially in their early teens, with their understanding in the future being able to mobilize and develop a young generation who loves the Al-Qur'an.